Competitive analysis in the express industry of Bangladesh: whether existing service features are satisfying customers or not - Chowdhury, Shaiyaz (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration,2014.